Trends in maternal body mass index in Northern Ireland: a cross-sectional and longitudinal study. Issue 4 (23rd December 2021) - Kent, Lisa; Cardwell, Christopher; Young, Ian; Eastwood, Kelly-Ann
Abstract : Objectives: Explore (1) associations between maternal body mass index (BMI), demographic and clinical characteristics, (2) longitudinal trends in BMI, (3) geographical distributions in prevalence of maternal overweight and obesity. Design: Retrospective population-based study. Setting: Linked, anonymised, routinely collected healthcare data and official statistics from Northern Ireland. Participants: All pregnancies in Northern Ireland (2011–2017) with BMI measured at ≤16 weeks gestation. Methods: Analysis of variance and χ 2 tests were used to explore associations. Multiple linear regression was used to explore longitudinal trends and spatial visualisation illustrated geographical distribution. Main outcomes are prevalence of overweight (BMI ≥25 kg/m 2 ) and obesity (BMI ≥30 kg/m 2 ). Results: 152 961 singleton and 2362 multiple pregnancies were included. A high prevalence of maternal overweight and obesity in Northern Ireland is apparent (singleton: 52.4%; multiple: 48.3%) and is increasing. Obesity was positively associated with older age, larger numbers of previous pregnancies and unplanned pregnancy (p<0.001). BMI category was also positively associated with unemployment (35% in obese class III vs 22% in normal BMI category) (p<0.001). Higher BMI categories were associated with increased rate of comorbidities, including hypertension (normal BMI: 1.8% vs obese III: 12.4%), diabetes mellitus (normal BMI: 0.04% vs obese III: 1.29%) and mental ill-health (normal BMI: 5.0% vs obese III: 11.8%) (p<0.001). Prevalence of maternal obesity varied with deprivation (most deprived: 22.8% vs least deprived: 15.7%) (p<0.001). Low BMI was associated with age <20 years, nulliparity, unemployment and mental ill-health (p<0.001). Conclusions: The prevalence of maternal BMI >25 kg/m 2 is increasing over time in Northern Ireland. Women are entering pregnancy with additional comorbidities likely to impact their life course beyond pregnancy. This highlights the need for prioritisation of preconception and inter-pregnancy support for management of weight and chronic conditions.